Digitalizing Local Wisdom: The Development of Tri Hita Karana-Integrated Hypermedia for Pancasila Education - Dina Fitri Rahayu; I Nengah Suastika; Desak Putu Parmiti (Jurnal Paedagogy, 2026)
This study aims to design and develop a Tri Hita Karana-based hypermedia learning resource for sixth-grade elementary school students and to evaluate its validity, practicality, and effectiveness in improving learning achievement in Pancasila Education. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The validity of the developed product was assessed using the Learning Object Review Instrument (LORI) by media and subject matter experts. Practicality was evaluated through the User Experience Questionnaire (UEQ), while effectiveness was examined using a pre-experimental one-group pretest–posttest design. Data on students’ learning achievement in Pancasila Education were collected through achievement tests and analyzed using a one-tailed t-test. The developed hypermedia consists of a cover page, user instructions, learning objectives, developer profile, learning materials, interactive quizzes, student reflection activities, and references. The content integrates the core concepts of Tri Hita Karana—Parhyangan, Pawongan, and Palemahan—through various multimedia elements, including text, images, audio, videos, animations, and interactive Wordwall-based quizzes connected through hyperlinks. The validation results indicated a mean score of 4.60, demonstrating that the product was highly valid. The practicality assessment yielded mean scores of 2.73 from teachers and 2.76 from students, both categorized as very practical. The effectiveness test showed a t-value of 83.467, which exceeded the critical t-value of 1.703, indicating a significant improvement in students’ learning achievement after using the Tri Hita Karana-based hypermedia. These findings suggest that the developed hypermedia is valid, practical, and effective for supporting Pancasila Education learning. The study contributes to the integration of Tri Hita Karana values into interactive digital learning media, making Pancasila Education more contextual, meaningful, and relevant to character-based learning in elementary education.